Clinical outcome of laparoscopic versus robot-assisted radical cystectomy for patients with bladder cancer: a retrospective study - Yuchen Bai (BMC, 2021)
Abstract Background With the development of minimally invasive surgery technology, patients with bladder cancer are increasingly receiving laparoscopic radical cystectomy (LRC) or robotic-assisted radical cystectomy (RARC) treatment. The main purpose of this study was to compare the long-term outcomes of bladder cancer patients treated with LRC versus RARC. Methods A retrospective study to identify patients with clinical stage Ta/T1/Tis to T3 bladder cancer who underwent RARC or LRC has been performed. The perioperative outcome, recurrence, and overall survival (OS) of the two surgical methods were compared. Results 218 patients were identified from March 2010 to December 2019 in our department, which including 82 (38%) patients who received LRC and 136 (62%) patients who received RARC. There was no significant difference between the two groups in terms of lymph node collection, lymph node positive rate, resection margin positive rate, and postoperative pathological staging. Compared with the LRC group, patients in the RARC group had a median estimated blood loss (180 vs. 250 ml; P = 0.02) and reduced complications at 90 days postoperatively (30.8% vs. 46.3%; P = 0.01). Recurrence, all-cause death, and cancer-specific death occurred in 77 (35%), 55 (25%), and 39 (18%) patients, respectively. The 5-year OS rate was 54.63% and 54.65% in the RARC and LRC group (P > 0.05). The 5-year cancer-specific survival (CSS) rate was 73.32% and 61.55% in RARC and LRC group (P > 0.05). There was no significant difference in OS [hazard ratio (HR) 1.083, 95% confidence interval (CI) 0.626–1.874; P = 0.78], and CSS (HR 0.789, 95%CI 0.411–1.515; P = 0.61) between two groups. Conclusions Both RARC and LRC were safe and effective with a similar long-term clinical outcomes. Moreover, RARC had significantly lower median estimated blood loss and reduced postoperative complications.